Accuracy of the general practitioner's sense of alarm when confronted with dyspnoea and/or chest pain: a prospective observational study. Issue 2 (18th February 2020) - Barais, Marie; Fossard, Emilie; Dany, Antoine; Montier, Tristan; Stolper, Erik; Van Royen, Paul
Abstract : Objectives: Dyspnoea and chest pain are symptoms shared with multiple pathologies ranging from the benign to life-threatening diseases. A Gut Feelings Questionnaire (GFQ) has been validated to measure the general practitioner's (GPs) sense of alarm or sense of reassurance. The aim of the study was to estimate the diagnostic test accuracy of GPs' sense of alarm when confronted with dyspnoea and chest pain. Design and settings: Prospective observational study in general practice. Participants: Patients aged between 18 and 80 years, consulting their GP for dyspnoea and/or chest pain, were considered for enrolment. These GPs had to complete the GFQ immediately after the consultation. Primary outcome measures: Life-threatening and non-life-threatening diseases have previously been defined according to the pathologies or symptoms in the International Classification of Primary Care (ICPC)-2 classification. The index test was the sense of alarm and the reference standard was the final diagnosis at 4 weeks. Results: 25 GPs filled in 235 GFQ questionnaires. The positive likelihood ratio for the sense of alarm was 2.12 (95% CI 1.49 to 2.82), the negative likelihood ratio was 0.55 (95% CI 0.37 to 0.77). Conclusions: Where the physician experienced a sense of alarm when a patient consulted him/her for dyspnoea and/or chest pain, the post-test odds that this patient had, in fact, a life-threatening disease was about twice as high as the pretest odds. Trial registration number: NCT02932982 .